(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
A simple accurate and rapid reversed phase high performance liquid chromatographic method has been developed and validated for the determination of four nonsteroidal anti-inflammatory drugs; Piroxicam(PX), Naproxen(NAP), Diclofenac sodium(DCL) and Mefenamic acid(MFNC) in their pure form and different commercial pharmaceutical formulation. The separation was performed on a NUCLEODUR® 100-5 C18ec (250 × 4.6 mm i.d.; particle size 5 μm) column as stationary phase with a mobile phase comprising of acetonitrile: deionized water acidified with 1% acetic acid in gradient mode. The flow rate was 1.5 mL.min-1 at the temperature 35 ºC and detection was carried out at 264 nm. Separation has been completed within 8 min. The retention times of Piroxicam, Naproxen, Diclofenac sodium, and Mefenamic acid were 4.267 min, 4.785 min, 6.555 min, and 7.683 min respectively. The linearity for Piroxicam was in the range of 3–200 μg.mL-1 and for Naproxen and Mefenamic acid was in the range 1-200 μg.mL-1, while for Diclofenac sodium was in the range 1.5–200 μg.mL-1. The proposed method was successfully applied for the determination of these drugs in their pure form and different pharmaceutical preparations (tablets, capsules, and ampoule) and there is no interference with additives.